Architectural morphology study towards sustainable design solutions (case study of Ha Noi children's palace design) - Doan Minh Khoi; Doan Minh Thu; Doan Thanh Binh (Tạp chí Khoa học và Công nghệ)
Researching building architectural morphology is one of the important tasks of architectural design, not only referring to formal design but also related to factors affecting form such as function organization, technical structure, technology implementation. Sustainable design is not only a current trend but also a goal that designs should aim for in order to minimize environmental impacts, save energy as well as to preserve and promote cultural values. This article studies the dialectical relationship between architectural form and sustainable design solutions. The methods used in this paper include systematic and logical analysis methods, diagramming methods, and empirical research methods through the case study of the design of the Hanoi Children's Palace – a construction that was recently completed in July 2024.